1998
DOI: 10.1116/1.581522
|View full text |Cite
|
Sign up to set email alerts
|

Seeded pulsed supersonic molecular beam growth of silicon carbide thin films

Abstract: Articles you may be interested inNon-adiabatic ab initio molecular dynamics of supersonic beam epitaxy of silicon carbide at room temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…These conditions correspond to those found in the growth experiment. 4 The sticking coefficients do not change substantially with increasing kinetic energy of the adatoms. The sticking probability for Si on 6H-SiC͑0001͒ is high and nearly constant, while we find a slight increase on 6H-SiC(0001 ), although always Ϸ20% smaller than the first.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These conditions correspond to those found in the growth experiment. 4 The sticking coefficients do not change substantially with increasing kinetic energy of the adatoms. The sticking probability for Si on 6H-SiC͑0001͒ is high and nearly constant, while we find a slight increase on 6H-SiC(0001 ), although always Ϸ20% smaller than the first.…”
mentioning
confidence: 95%
“…In contrast with other techniques, high quality epitaxial films can be grown at lower substrate temperatures, which promotes sharp interfaces and limits diffusion of dopants. It was recently demonstrated that high quality single polytype films can be deposited at improved growth rates on 6H-SiC substrates maintained at 1530 K. 4 Many aspects of SJMB growth are not yet well understood. To our knowledge, there has been no report of computer simulations of SJMB growth of SiC.…”
mentioning
confidence: 99%